Budidaya Ternak Babi Fase Starter dengan Penggunaan Sumber Pakan Konsentrat yang Berbeda di Kabupaten Tana Toraja - Tala, Selfin; Irfan, Muhammad (Journal Galung Tropika, 2020)
Pig livestock in Tana Toraja and North Toraja Regencies are made as a side business, especially by mothers and carried on for generations. Every morning the pork vegetables were picked and then processed with rice milling bran to become feed. Pork vegetable is the local name’s for sweet potato leaves (Ipomea batatas). Generally, pig farmer’s use concentrates mixed with yellow corn and smooth bran, which are referred to as local concentrates. Traditional breeders in Tana Toraja still use a number of concentrates which depend on the availability of feed. This study aimed to determine the effect of several types of concentrates on the performance of starter age pigs. The study used 9 male pigs and placed in 9 individual cage units and arranged in a Randomized Block Design (RBD), consisting of 3 treatments and 3 treatment groups based on body weight. The treatments consist of Local Concentrate + Pork Vegetable (P1), Local Concentrate + Factory Concentrate + Pork Vegetable (P2), and the Factory Concentrate (P3) by grouping based on body weight. The variables measured were diet consumption, weight gain, and efficiency of ration use. The results showed that the treatment had a significant effect (P <0.05) on Weight Gain, Consumption, and Ration Efficiency. The use of concentrated sources by mixing local concentrates, factor concentrates, and pork vegetables give the best for starter phase pigs.